Response Rate and Toxicity of Docetaxel / Cisplatin /5FU in Comparison with Cisplatin / 5FU Induction Chemotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma - Azghandi, Samira; Ameri, Ahmad; Taghi Khorsand, Mohammad; Karimi, Ebrahim; Yazdani, Nasrin; Haghighatkhah, Hamid Reza; Malekshoar, Mehran (Reports of Radiotherapy and Oncology, 2025)
Background: Response to chemotherapy is a reliable marker for radiation sensitivity in patients with locally advanced head and neck squamous cell carcinoma. We compared the response rate and toxicity after two cycles of chemotherapy using Docetaxel / Cisplatin /5FU or Cisplatin / 5FU among these patients. Methods: We randomly assigned 16 to 75 years old patients with stage III or IV non-metastatic locally advanced head and neck squamous cell carcinoma to receive either DCF or CF every 3 weeks for two cycles. All patients who received at least one and two cycles of chemotherapy were considered for toxicity and response evaluation respectively. Results: Seventy patients underwent randomization, 36 and 34 patients were assigned to Docetaxel / Cisplatin /5FU and Cisplatin / 5FU groups respectively. Three and 8 patients were excluded after randomization and before receiving any chemotherapy in Docetaxel / Cisplatin /5FU and Cisplatin / 5FU groups respectively. Finally 30 and 25 in Docetaxel / Cisplatin /5FU group and 25 and 23 patients in Cisplatin / 5FU group were evaluated for toxicity and response respectively. Response rate (complete and partial response) was %83 (35% complete and 48% partial response) and %84(16% complete and 68% partial response) in Cisplatin / 5FU and Docetaxel / Cisplatin /5FU groups respectively (P= 0.28). There was no differences in complete response rate between two groups (P=0.18). Neutropenia, phlebitis and mucositis were more common in Cisplatin / 5FU group without statistically significant difference. Constipation was significantly more common in Cisplatin / 5FU group (P= 0.008). Diarrhea, alopecia and febrile neutropenia were significantly more common in Docetaxel / Cisplatin /5FU group (P= 0.006, 0.01 and 0.03 respectivly). Conclusion: We could not find any significant differences between response to Docetaxel / Cisplatin /5FU and Cisplatin /5FU combination chemotherapy among Iranian patients with locally advanced head and neck squamous cell carcinoma. However, for better evaluation, larger studies with better designs are being conducted in our center.